ANALISIS LATIHAN SPRECHEN A1 DALAM SITUS WWW.LEARNGERMAN.DW.COM - Ahmad Hanif; Amir Amir; Ending Khoerudin (Jurusan Pendidikan Bahasa Jerman FPBS UPI, 2023)
When learning German, there are four essential skills to master: Listening (HÃ¶ren), Reading (Lesen), Speaking (Sprechen), and Writing (Schreiben). Each of these skills presents its own level of difficulty, with Speaking (Sprechen) often proving challenging to attain proficiency in. Consequently, the need for alternative, freely accessible learning resources to facilitate the learning process arises. One such valuable resource is www.learngerman.dw.com, which offers a unique feature of continuous speaking exercises alongside other skill exercises. This study aims to accomplish the following objectives: 1) Describe the types of Speaking (Sprechen) exercises available on the website www.learngerman.dw.com. 2) Outline the steps required to complete the Speaking (Sprechen) exercises found on the same website. 3) Evaluate the Speaking (Sprechen) exercises on www.learngerman.dw.com using the Kriterienkatalog fur Internet-Lernmaterial Deutsch als Fremdsprache. This research employs a descriptive analysis methodology to achieve its goals. The analysis of Sprechen exercises on the website is based on Schatz's theory. The findings indicate that 1) The website offers 411 vorbereitende Ãœbungen and 97 aufbauend und strukturierend exercises, with simulierend exercises being unavailable. 2) The steps for completing the A1 Speaking (Sprechen) exercise on the website vary, but they all begin with watching a video. 3) The Speaking (Sprechen) exercises on www.learngerman.dw.com meet 13 out of 18 criteria outlined in the Kriterienkatalog fur Internet-Lernmaterial Deutsch als Fremdsprache, affirming its potential as an effective alternative learning resource for enhancing speaking skills.